Implementasi Strategi Telesales dalam Efektivitas Penjualan Retail Lotte Grosir Bandung - Ana Novianti; Firman Yudhanegara (INDO PUBLISHING, 2026)
The increasingly competitive retail business environment requires companies to implement effective marketing strategies to maintain customer relationships and improve sales performance. One of the strategies employed is telesales, a direct marketing activity that enables companies to communicate with customers, build business relationships, and increase sales opportunities. This study aims to analyze the implementation of telesales strategies in supporting sales effectiveness at the Retail Division of Lotte Grosir Bandung. The research employed a descriptive qualitative approach. Data were collected through semi-structured interviews with a telesales staff member as the key informant and direct observation during the internship program. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that telesales strategies are implemented through the utilization of customer purchase history data, personalized communication, and product recommendations tailored to customer needs. Telesales contributes to sales effectiveness by improving the accuracy of sales targeting and maintaining long-term customer relationships. The main challenges include price competition, customers’ limited availability for communication, and differences in telesales communication skills. Therefore, optimizing customer data utilization, enhancing communication skills through training, and implementing Customer Relationship Management (CRM) are essential efforts to improve telesales effectiveness.